Hands of time : a watchmaker's history - Struthers, Rebecca (Harper, an imprint of HarperCollinsPublishers, 2023)
An award-winning British watchmaker takes readers on a journey through the history of time-keeping, from the earliest attempts to keep track of the passing of days to the engineering breakthrough that created the first watch.